2011
DOI: 10.2174/187152711794653797
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine in Neurological Disease: A Marker or a Cause?

Abstract: Hyperhomocysteinemia is increasingly recognized as an independent risk factor for several cerebral, vascular, ocular, and agerelated disorders. Whether it is a cause or a consequence or a mere marker necessitates further clarification. This review focuses on the pathophysiological aspects of homocysteine's involvement in neurodegenerative and neuropsychiatric disorders and complications. The pharmacological agents (antiepileptic drugs, L-DOPA) augment the homocysteine levels, thus, raising concern for physicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 105 publications
(125 reference statements)
0
5
0
Order By: Relevance
“…Sener et al (2) found that epilepsy itself will not increase the homocysteine level. However, a current study found that long-term treatment of antiepileptic drugs would cause metabolic abnormalities in patients, causing the increase of homocysteine (Hcy) concentration (3), and they further indicated that about 10% to 40% of patients with epilepsy might have hyperhomocysteine (Hhcy) (4) al. (5) showed that Hhcy caused vascular endothelial dysfunction, thrombosis, cholesterol, disorder of triglyceride synthesis and metabolism, and the activation of monocytes, which all can contribute to sclerosing disease including the occurrence and progression of glomerulosclerosis.…”
Section: Introductionmentioning
confidence: 96%
“…Sener et al (2) found that epilepsy itself will not increase the homocysteine level. However, a current study found that long-term treatment of antiepileptic drugs would cause metabolic abnormalities in patients, causing the increase of homocysteine (Hcy) concentration (3), and they further indicated that about 10% to 40% of patients with epilepsy might have hyperhomocysteine (Hhcy) (4) al. (5) showed that Hhcy caused vascular endothelial dysfunction, thrombosis, cholesterol, disorder of triglyceride synthesis and metabolism, and the activation of monocytes, which all can contribute to sclerosing disease including the occurrence and progression of glomerulosclerosis.…”
Section: Introductionmentioning
confidence: 96%
“…Indeed, recent study have con rmed a negative role for a histone deacetylase inhibitor, valproic acid(VPA) on BMD of trochanter and Ward's triangle, when administered for 24 months [9]. Potential mechanisms for bone loss after antiepileptic drugs treatment include vitamin D insu ciency, hyperparathyroidism, calcitonin de ciency, and inhibition of intestinal calcium absorption, and other hormonal changes [10,11]. Silibinin (SIM) is speci c inhibitor of 3-Hydroxy-3-methylglutarylcoenzyme A (HMG-CoA) that is widely used to reduce plasma cholesterol levels and prevent cardiovascular diseases [12].…”
Section: Introductionmentioning
confidence: 99%
“…Folate deficiency is reported to be present in 29% of the patients with cardiovascular diseases 15. Both B12 and folate deficiency entail hyper-homocysteinaemia (HHC), which is also a risk factor for neurological disorders 16. In addition, preoperative HHC is associated with worse postoperative outcomes 17…”
Section: Introductionmentioning
confidence: 99%